2001
DOI: 10.1212/wnl.57.6.1071
|View full text |Cite
|
Sign up to set email alerts
|

EEG criteria predictive of complicated evolution in idiopathic rolandic epilepsy

Abstract: Different combinations of at least three of six distinctive interictal EEG patterns and their long-lasting (> or =6-month) persistence seem to be the hallmarks of patients with BECTS at risk for neuropsychological impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
257
1
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(276 citation statements)
references
References 34 publications
10
257
1
8
Order By: Relevance
“…In contrast to CZP, no EEG normalization could be found in the 10 patients treated with CBZ in that study. In addition, CBZ may have the disadvantage of worsening EEG characteristics and precipitating of epilepsy with continuous spikes and waves during slow sleep (CSWS) in a considerable number of patients (3,4,(9)(10)(11)(12)(13), although this influence is controversial (14). Early observations showed positive effects of STM treatment on the interictal EEG in BECTS (2,11,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to CZP, no EEG normalization could be found in the 10 patients treated with CBZ in that study. In addition, CBZ may have the disadvantage of worsening EEG characteristics and precipitating of epilepsy with continuous spikes and waves during slow sleep (CSWS) in a considerable number of patients (3,4,(9)(10)(11)(12)(13), although this influence is controversial (14). Early observations showed positive effects of STM treatment on the interictal EEG in BECTS (2,11,15).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports point to the role of interictal EEG changes for developing neuropsychological deficiencies in BECTS (3,4). As the disease is associated with a wide variability of intraindividual EEG courses, including spontaneous normalization (5), a blinded, placebo-controlled investigation is necessary for analyzing drug effects on the EEG in BECTS.…”
mentioning
confidence: 99%
“…The frequency of different group of EEG wave patterns are as shown in fig III. The relationship of various types of seizures with EEG-patterns showed that concordance and discordance EEG findings such as clinically diagnosed primarily generalized seizure n= 327, 145(discordance rate of 44.34%) had normal EEG, and 182 (concordance 55.66%), partial seizures with secondary generalization n=284, abnormal EEG were found in 73 (concordance 25.7%) normal EEG in 211,(discordance74.3%), partial seizure n= 46, abnormal EEG was in 29( concordance of 63.04%) and normal in 17 ( discordance of 36.96%) and complex partial seizure n=72 normal EEG in 31 (discordance of 43.06%)and abnormal EEG of 41(concordance of 56.94%). 14 found the EEG-abnormalities were epileptiform activity, in 54%of the cases. AlSuleiman (2001) 15 , found the EEG-abnormalities were epileptiform activity, in 51%of the cases.…”
Section: Resultsmentioning
confidence: 90%
“…Earlier studies disclosed that the disruptive effect of a single IED is directly proportional to the voltage of the wave but not the spike (Shewmon and Erwin, 1988c). This observation and the direct relationship between the spatio-temporal amount of the spikewave series and the severity of the deficit symptoms in the long run (Metz-Lutz et al, 1999;Baglietto et al, 2001;Massa et al, 2001) are independently derived findings but lead to the same conclusion: the greater the degree of neuronal synchronization over time and space the greater the cortical dysfunction. As to avoid confusion in this paper "synchronization" refers to the synchronous activation of great cortical neuronal masses (Nunez, 1995), the result of which is reflected by the increase of the voltage of the EEG signal (Pfurtscheller and Lopes da Silva, 1999).…”
Section: The Importance and The Assessment Of "Synchronization"mentioning
confidence: 86%
“…However, other investigators described fluctuating neurological symptoms, disturbed speech and cognitive impairment that were related to the presence of frequent IEDs but not strictly time-locked to them. Drug treatment that abolished the spikes caused significant clinical improvement within a short time period (Hirsch et al, 1990;Metz-Lutz et al, 1999;Baglietto et al, 2001;Massa et al, 2001;Dalla Bernardina et al, 2002). Thus, a "delayed effect" of the IEDs might be deductively postulated as an explanation for the lack of the precise temporal coincidence between the IEDs and the time course of the above mentioned symptoms.…”
Section: Introductionmentioning
confidence: 99%